Advances in information storage systems - Bhushan,Bharat (Massachusetts World Scientific, 1995)
This volume contains 30 articles covering various aspects of theinformation storage and processing industry. It is organized intothree parts: Mechanics and Tribology of Magnetic Rigid Disk Drives;Dynamics and Controls of Magnetic Rigid Disk Drives; and Mechanics ofFlexible Media Systems.
Keywords: Cơ bản